Quantitative Reverse Sample Genome Probing of Microbial Communities and Its Application to Oil Field Production Waters - Voordouw, Gerrit (1993)
This paper presents a protocol for quantitative analysis of microbial communities by reverse sample genome probing is presented in which (i) whole community DNA is isolated and labeled in the presence of a known amount of an added internal standard and (ii) the resulting spiked reverse genome probe is hybridized with a master filter on which denatured genomic DNAs from bacterial standards isolated from the target environment were spotted in large amounts (up to 1,500 ng) in order to improve detection sensitivity. This protocol allowed reproducible fingerprinting of the microbial community in oil field production waters at 19 sites from which water and biofilm samples were collected. It appeared that selected sulfate-reducing bacteria were significantly enhanced in biofilms covering the metal surfaces in contact with the production waters.